Evaluating community pharmacists’ involvement in patient counselling and health education in Nairobi, Kenya: A cross-sectional study - Seraphine Wanjiro Manjari; Mergia Terefe Ermias (PLoS ONE, 2026)
Background Community pharmacists serve as the most accessible healthcare providers, playing a pivotal role in patient counselling, health education, and disease prevention. Despite their critical function in the healthcare system, limited research has examined their actual involvement in these areas within Nairobi, Kenya. This study aimed to assess community pharmacists’ engagement in patient counselling and health education, comparing self-reported practices with observed behaviours using a simulated patient approach. Methods This study employed a cross-sectional descriptive design incorporating both structured questionnaires and a simulated patient (SP) methodology to compare self-reported and observed counselling practices among registered community pharmacies in Nairobi. Sixty pharmacies were randomly selected, and forty-eight pharmacists completed the study. Data were collected using structured questionnaires that assessed pharmacists’ self-reported counselling and health education practices, alongside simulated patient visits that evaluated actual pharmacist–patient interactions. The case scenarios included a request for diabetes medication without a prescription, an over-the-counter acne treatment request, and a consultation for severe acne. These encounters were used to assess counselling competence, regulatory adherence, and patient education. Data were analysed using descriptive statistics to compare self-reported practices with observed behaviours. Results While 66.7% of pharmacists reported providing detailed counselling, only 26.7% of simulated visits reflected this practice. Additionally, 75% of pharmacists provided minimal verbal counselling beyond stating the drug name and dosage. Patient satisfaction levels were low, with most simulated patients rating their encounters poorly on a 20-point scale. Conclusion The study underscores critical gaps in patient counselling, health education, and adherence to prescription regulations among community pharmacists in Nairobi. The disconnect between self-reported and observed counselling practices suggests the need for targeted training programs to enhance pharmacists’ communication skills, regulatory compliance, and disease prevention counselling. Strengthening enforcement mechanisms and integrating patient-centred education strategies in pharmacy curricula are essential to optimizing pharmacists’ roles in healthcare. These findings highlight the need for targeted training and regulatory enforcement to strengthen pharmacists’ roles in patient counselling and health education in Nairobi.